QUANTUM-DIMENSIONAL EFFECTS IN THERMOELECTRIC CHARACTERISTICS OF LEAD CHALCOGENIDES NANOSTRUCTURES - D.M. Freik; I.K. Yurchyshyn; V.Yu. Potyak (Vasyl Stefanyk Precarpathian National University, 2014)
On the basis of theoretical model of quantum well (QW) with infinitely high walls it was investigated thermoelectric parameters depending on the thickness of the layer of nanostructures IV-VI (PbS, PbSe, PbTe) in the approximation of changing Fermi energy. There have been shown that the dependences of the Seebeck coefficient, electrical conductivity and thermoelectric power factor on well width for lead chalcogenides nanofilms are in good agreement with the experimental data. So, that proves the correctness of used model.